International spillovers of monetary policy: Lessons from Chile, Korea, and Poland. (February 2019) - Gajewski, Krzysztof; Jara, Alejandro; Kang, Yujin; Mok, Junghwan; Moreno, David; Serwa, Dobromił
Abstract: In this paper, we assess evidence on international monetary policy spillovers to domestic bank lending in Chile, Korea, and Poland, using confidential bank-level data and different measures of monetary policy shocks in relevant currency areas. These three emerging market economies are small and open, their banking systems do not have significant presence overseas, and they can be considered as price takers in the world economy. Such features allow for better identification of binding financial constraints and foreign monetary policy shocks. We find that the monetary policy shocks spill over into domestic bank lending, modifying the degree to which financial frictions tighten or relax, and this evidence is consistent with international bank lending and portfolio channels.